Analisis Semiotika Gaya Bahasa dalam Program Sie Reuboh LPP-RRi Banda Aceh - Cut Melsa Miranti (Penerbit Goodwood, 2022)
Purpose: There are many problems that occur in the pronunciation and delivery of information both in writing and orally and visually. This happens because there is no filter in language style, therefore language style is needed with the aim that every information conveyed can be digested and consumed properly by listeners according to the age level of the listener Method: This scientific work is a descriptive study use a qualitative approach. using survey, interview, and recording methods. In collecting data the researchers used several interrelated and complementary techniques, namely, observation, interviews, recording and documentation. Results: Intern students are directly involved in the process of covering the media. In this study, while the researchers listened to several parts, namely the recorded documentation on May 14, 2022 that the entire “Sie Reuboh” programme used standard and formal language calls. The researcher concludes that the use of language style in a communication process, especially in this popular voice programme, uses several language styles to convey and explain meaning without having to use excessive word stress. Limitations: The limitation in this study lies in the search for references to previous studies because research on semiotic analysis of language style in the form of sound is still very rarely studied. and data retrieval during recording. Researchers had difficulty during interviews because of the broadcaster's schedule not every day. This research in the future will also cover other radio programs. Contribution: The result language style is more to mediate and straighten out the problems that exist between the communicator and the communicant.